Mitochondria in mesenchymal stem cell biology and cell therapy: From cellular differentiation to mitochondrial transfer - Hsu, Yi-Chao; Wu, Yu-Ting; Yu, Ting-Hsien; Wei, Yau-Huei (Seminars in cell & developmental biology, 2016)
•An integrated view on different protein kinases and sirtuins in MSCs is provided.•The regulation of mitochondrial biogenesis and metabolism in MSCs are summarized.•Recent advances in mitochondrial dynamics and transfer are discussed. Mesenchymal stem cells (MSCs) are characterized to have the capacity of self-renewal and the potential to differentiate into mesoderm, ectoderm-like and endoderm-like cells. MSCs hold great promise for cell therapies due to their multipotency in vitro and therapeutic advantage of hypo-immunogenicity and lower tumorigenicity. Moreover, it has been shown that MSCs can serve as a vehicle to transfer mitochondria into cells after cell transplantation. Mitochondria produce most of the energy through oxidative phosphorylation in differentiated cells. It has been increasingly clear that the switch of energy supply from glycolysis to aerobic metabolism is essential for successful differentiation of MSCs. Post-translational modifications of proteins have been established to regulate mitochondrial function and metabolic shift during MSCs differentiation. In this article, we review and provide an integrated view on the roles of different protein kinases and sirtuins in the maintenance and differentiation of MSCs. Importantly, we provide evidence to suggest that alteration in the expression of Sirt3 and Sirt5 and relative changes in the acylation levels of mitochondrial proteins might be involved in the activation of mitochondrial function and adipogenic differentiation of adipose-derived MSCs. We summarize their roles in the regulation of mitochondrial biogenesis and metabolism, oxidative responses and differentiation of MSCs. On the other hand, we discuss recent advances in the study of mitochondrial dynamics and mitochondrial transfer as well as their roles in the differentiation and therapeutic application of MSCs to improve cell function in vitro and in animal models. Accumulating evidence has substantiated that the therapeutic potential of MSCs is conferred not only by cell replacement and paracrine effects but also by transferring mitochondria into injured tissues or cells to modulate the cellular metabolism in situ. Therefore, elucidation of the underlying mechanisms in the regulation of mitochondrial metabolism of MSCs may ultimately improve therapeutic outcomes of stem cell therapy in the future.